THE URGENCY OF ECONOMIC LAW IN PROVIDING PROTECTION FOR THE POOR, NEGLECTED CHILDREN, AND OTHER VULNERABLE GROUPS AS MANDATED BY THE CONSTITUTION: A LITERATURE STUDY - Gunawan Widjaja (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This research aims to analyse the urgency of economic law in providing protection for the poor, abandoned children, and other vulnerable groups as mandated by the constitution, particularly Article 34 of the 1945 Constitution. Through a literature study approach, this research examines various regulations, policies and social protection programmes that have been implemented in Indonesia. The results show that economic law plays an important role in ensuring access to justice, social protection and equal opportunities for vulnerable groups. However, the implementation of economic law protection still faces various obstacles, such as budget constraints, the complexity of legal procedures, low legal literacy, and structural discrimination. This research recommends strengthening regulations, increasing the capacity of implementing agencies, synergising between agencies, and empowering vulnerable groups so that economic legal protection can run effectively and fairly as mandated by the constitution.